Effects of Spontaneous Symmetry Break in the Origin of Non-analytic Behavior of Entanglement at Quantum Phase Transitions - Pereira, Leonardo J.; de Oliveira, Thiago R. (Frontiers in Physics, 2016)
We present an example where spontaneous symmetry breaking may affect not only the behavior of the entanglement at Quantum Phase Transitions, but also the origin of its non-analyticity. In particular, in the XXZ model, we study the non-analyticities in the concurrence between two spins, which was claimed to be accidental since it had its origin in the optimization involved in the concurrence definition. We show that when one takes into account the effect of the spontaneous symmetry breaking, even though the values of the entanglement measure does not change, the origin of the non-analytical behavior changes. The non-analytical behavior is not due to the optimization process anymore and in this sense it is a "natural" non-analyticity. This is a much more subtle influence of the spontaneous symmetry breaking not observed before. We also show that the value of entanglement between one site and the rest of the chain changes after taking into account the spontaneous symmetry breaking.